1998
DOI: 10.1093/nar/26.3.703
|View full text |Cite
|
Sign up to set email alerts
|

The role of zinc finger linkers in p43 and TFIIIA binding to 5S rRNA and DNA

Abstract: Transcription factor IIIA (TFIIIA) and p43 zinc finger protein form distinct complexes with 5S ribosomal RNA in Xenopus oocytes. Additionally, TFIIIA binds the internal promoter of the 5S RNA gene and supports assembly of a transcription initiation complex. Both proteins have nine tandemly repeated zinc fingers with almost identical linker lengths between corresponding fingers, yet p43 has no detectable affinity for the 5S RNA gene. TFIIIA zinc fingers 1-3 are connected by highly conserved linkers, first ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
1
32
0
1
Order By: Relevance
“…It has been previously observed that certain amino acid linker sequences connecting tandem repeats of C2H2 domains were highly correlated with ZF-DNA binding (Laity et al, 2000;Ryan and Darby, 1998). In mammals, tandem ZFs are frequently separated by linkers of 5 amino acids, with roughly 50% of these having the sequence TGEKP (Wolfe et al, 2000).…”
Section: Linker Characterizationmentioning
confidence: 99%
“…It has been previously observed that certain amino acid linker sequences connecting tandem repeats of C2H2 domains were highly correlated with ZF-DNA binding (Laity et al, 2000;Ryan and Darby, 1998). In mammals, tandem ZFs are frequently separated by linkers of 5 amino acids, with roughly 50% of these having the sequence TGEKP (Wolfe et al, 2000).…”
Section: Linker Characterizationmentioning
confidence: 99%
“…Indeed, the conservation of this sequence allowed cDNAs encoding many zinc finger proteins to be identified before genomic sequencing efforts (3). Although structural studies (4-7) and mutagenesis experiments (8)(9)(10)(11)(12) have suggested a role for the linker in DNA binding, it has been noted that this contribution is relatively minor and probably insufficient to explain the high degree of evolutionary conservation of the linker sequence (10).…”
mentioning
confidence: 99%
“…However, as discussed elsewhere, the structural and dynamic characteristics dictating the functional role of ZFs are poorly understood (40). Tandems of ZFs are generally separated by highly conserved TGEKP sequence linkers that have been shown to be important for optimal DNA binding (18,19,42,43). Accordingly, different groups have proposed that the nature of ZF tandem linkers could enable the prediction of their functions (18,19,44).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, series of ZFs are connected by highly conserved TGEKP sequence linkers and bind in sets of two or more in the major groove of the DNA with each ZF contacting three DNA bases. These linkers are important to allow for consecutive motifs to optimally fit in the major groove of DNA (18,19). Variations in the consensus sequence can significantly reduce binding affinity (18,19).…”
Section: Ink4mentioning
confidence: 99%
See 1 more Smart Citation